Congenital dislocation of patella in a preterm infant-a case report - Garg, Ayushi; Gill, Karambir Singh; Garg, Madhur (International Journal of Contemporary Pediatrics, 2022)
Congenital dislocation of patella (CDP) is a rare condition which manifests after birth and is diagnosed late in childhood when the patellar ossification has already occurred and symptoms start to develop in patients. The exact etiology of this disease is still unknown. Diagnosis at such a later age leads to associated conditions like contractures, genu valgum etc. This condition should be diagnosed and treated as soon as possible after birth to significantly reduce the associated complications and to restore the normal functioning of the knee joint. Although a number of papers have been published regarding congenital patellar dislocation in India, none of them have recognized this rare disorder early in infancy. This disorder can be easily missed on routine X-ray in infancy as the patella has not yet ossified. This case report represents the first CDP diagnosed at the age of 1.5 months in India, in a 1.5-month-old preterm male patient. The patient presented with no specific symptoms other than a right knee swelling and was diagnosed with congenital patellar dislocation at the early age of 1.5 months. Radiological investigations were carried out using venous Doppler and high-resolution ultrasound. Surgical correction is the only possible treatment of CDP and it should be done as soon as possible after diagnosing the condition to re-establish the normal operation of the affected knee joint.